Extraction and Spectrophotometric Determination of Cobalt - Chaudhari, R.A.; Sawant, A.D. (Asian Journal of Chemistry, 2010)
Isonitroso malon-di-anilide (HIMDA) is proposed as a new reagent for the selective extraction and photometric determination of Co(II). The reagent forms yellowish brown complex in the pH range 6.4 to 7. The complex can be extracted with chloroform and measured against solvent blank on spectronic λ20 at 410 nm. The effects of various experimental parameters such as pH, reagent concentration, equilibrium period and diverse ions have been studied and optimum conditions were evaluated to extract, separate and estimate cobalt at ppm level by spectrophotometry. The proposed method is selective and rapid for estimation of cobalt at trace level.